Analisis Dampak Media Sosial (Tiktok) Terhadap Akhlak Peserta Didik Di Sekolah Menengah Pertama Surabaya - Robbani, Danny Dwi; Moh Faizin (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The rapid growth of social media, particularly TikTok, has greatly influenced the lives of teenagers, including junior high school students. TikTok is popular for its creative and entertaining content, yet it also raises concerns regarding students’ morality. This phenomenon is important to study since junior high school students are in the stage of identity formation and are vulnerable to imitating behaviors from the digital environment. This study aims to analyze the impact of TikTok usage on the morality of class VII H students at SMP Negeri 5 Surabaya. A descriptive qualitative method was employed with data collected through questionnaires, interviews, observations, and documentation. The research subjects included VII H students, the homeroom teacher, parents, and student affairs management. The findings reveal that most students use TikTok for 1–5 hours daily with varied content. Positive impacts include enhanced creativity, entertainment, and additional knowledge. However, more dominant negative effects involve reduced politeness, procrastination, and language style changes. Therefore, the roles of teachers, parents, and schools are crucial in supervising and guiding students to use social media wisely.